Magnetic Permeability Perturbation Testing for Internal Axial Cracks in Small-Diameter Thick-Walled Steel Pipes - Xueyu Zhao; Zhiyang Deng; Zhiheng Yu; Tingyi Li; Xiaochun Song (Applied Sciences, 2023)
Special geometric features and complex working environments render the internal defects of small-diameter thick-walled steel pipes “easy to expand, difficult to detect”. In this paper, a magnetic permeability perturbation testing (MPPT) method is proposed to assess the internal axial cracks of small-diameter thick-walled steel pipes. The mechanism of the MPPT method and its corresponding probe and magnetizer are introduced, and its feasibility is verified through a series of simulations and experiments. Experiments conducted using different sizes of small-diameter thick-walled pipes show that this method offers good performance with respect to the detection of internal axial cracks. Additionally, both diameter and wall thickness significantly affect the MPPT signal. To a certain extent, a greater wall thickness or a smaller diameter brings about a weaker signal. This method does not benefit from the lift-off effect, nor is it limited by the skin effect, which has great practical value as a supplement to the evaluation of thick-walled steel pipes.